Persuasion profiles to promote pedestrianism: Effective targeting of active travel messages. (July 2020) - Pangbourne, Kate; Bennett, Sam; Baker, Al
Highlights: Age and personality trait predict potential uptake of persuasive walking messages. Message appeal value interacts with age and the agreeableness personality trait. Type of argument used in messages had no effect on their perceived persuasiveness. Even generally more persuasive values e.g. health vary by individual characteristics. The findings challenge other research on message persuasiveness and behaviour change. Abstract: This study recommends novel strategies for tailoring messages to encourage walking, for use in travel planning, Mobility as a Service platforms and other apps which promote sustainable transport behaviour. We suggest strategies based on individual demographic and psychosocial factors derived from the findings of a study of the persuasiveness of different arguments to encourage walking. 402 participants from across the UK were recruited to evaluate 16 pro-walking arguments systematically varied by type of argumentation used, and the values to which they appealed. We explored interactions between these argument features and participants' personality, travel attitude, age and recent transport mode usage. We report several interesting findings, including that the types of argumentation used, participants' travel attitude, and their previous transport uses all had no effect on the perceived persuasiveness of messages. Factors which did have an effect on the perceived persuasiveness of messages included the age and personality of the participants and the value to which the message appealed. We also found several complex interactions between these factors, such as that those higher in agreeableness tended to rate arguments emphasising environmental benefits as more persuasive, and that younger participants tended to rate arguments appealing to the health benefits and convenience of walking as less persuasive.